Introducing Membrane Charge and Membrane Potential to T Cell Signaling - Ma, Yuanqing; Poole, Kate; Goyette, Jesse; Gaus, Katharina (Frontiers in Immunology, 2017)
While membrane models now include the heterogeneous distribution of lipids, the impact of membrane charges on regulating the association of proteins with the plasma membrane is often overlooked. Charged lipids are asymmetrically distributed between the two leaflets of the plasma membrane, resulting in the inner leaflet being negatively charged and a surface potential that attracts and binds positively charged ions, proteins and peptide motifs. These interactions not only create a transmembrane potential, they can also facilitate the formation of charged membrane domains. Here we reference fields outside of immunology in which consequences of membrane charge are better characterised to highlight important mechanisms. We then focus on T cell receptor (TCR) signalling, reviewing the evidence that membrane charges and membrane-associate calcium regulate phosphorylation of the TCR-CD3 complex and discuss how the immunological synapse exhibits distinct patterns of membrane charge distribution. We propose that charged lipids, ions in solution and transient protein interactions form a dynamic equilibrium during T cell activation.